Associations between physical activity and energy and fatigue depend on sleep quality. Issue 4 (1st October 2020) - Miller, Matthew; Lee-Chambers, Jahnée; Cooper, Briana; Boolani, Ali; Jansen, Erica
ABSTRACT: Objective: Sleep and physical activity are independent predictors of energy and fatigue, but whether poor sleep quality moderates the association between physical activity and energy and fatigue remains unclear. Methods: A sample of 675 young adults (median age 20 years) was recruited from a university town and completed questionnaires regarding sleep quality (Pittsburgh Sleep Quality Index), typical weekly physical activity (moderate and high-intensity), and feelings of mental and physical energy and fatigue. Linear regression analyses were run to evaluate the associations between physical activity and sleep with the energy and fatigue outcomes, adjusting for sex, age, and caffeine. Interaction analyses were run and models were stratified by sleep quality to evaluate effect modification. Results: Participants reported a weekly median (Q1, Q3) of 4 h (2, 8) of high-intensity physical activity, and 1 h (0, 3) of moderate-intensity physical activity, and 50% of the sample had poor sleep quality. Physical activity was positively associated with physical and mental energy, and sleep quality was associated with each of the 4 outcomes. Interaction analyses revealed that high-intensity physical activity was positively related to physical energy only among those with good quality sleep. Further, high-intensity physical activity was more strongly positively associated with physical energy among those with good quality sleep than those with poor quality sleep ( β = 0.32 with 95% CI 0.18–0.46 compared to 0.14 with 95% CI −0.01, 0.29). Conclusion: Findings suggest that physical activity alone may not be able to overcome the deleterious effects of poor sleep on feelings of mental and physical energy and fatigue.